The hit - Baldacci, David; McLarty, Ron.; Cassidy, Orlagh (New York : Hachette Audio, 2013)
No one else can match will Robie's talents as a hitman. No one, except Jessica Reel. A fellow assassin, Reel is every bit as lethal as Robie. And now, she's gone rogue, turning her gun sights on other members of their agency. To stop one of their own, the U.S. government looks once again to Robie. His mission: bring in Reel, dead or alive. Only a killer can catch another killer, they tell him. but as Robie pursues Reel, he quickly finds that there is more to her betrayal than meets the eye.
Abridgement approved by author.
Read by Ron McLarty and Orlagh Cassidy.
PBK
Keywords: Assassins -- Fiction; Female assassins -- Fiction; Betrayal -- Fiction; Intelligence officers -- United States -- Fiction; Conspiracies -- Fiction; Suspense fiction; Assassins; Betrayal; Conspiracies; Intelligence officers; Suspense fiction; United States; Fiction